Klebsiella variicola Is a Frequent Cause of Bloodstream Infection in the Stockholm Area, and Associated with Higher Mortality Compared to K. pneumoniae - Maatallah, Makaoui; Vading, Malin; Kabir, Muhammad Humaun; Bakhrouf, Amina; Kalin, Mats; Nauclér, Pontus; Brisse, Sylvain; Giske, Christian G. (PloS one, 2014)
Clinical isolates of Klebsiella pneumoniae are divided into three phylogroups and differ in their virulence factor contents. The aim of this study was to determine an association between phylogroup, virulence factors and mortality following bloodstream infection (BSI) caused by Klebsiella pneumoniae. Isolates from all adult patients with BSI caused by K. pneumoniae admitted to Karolinska University Hospital, Solna between 2007 and 2009 (n = 139) were included in the study. Phylogenetic analysis was performed based on multilocus sequence typing (MLST) data. Testing for mucoid phenotype, multiplex PCR determining serotypes K1, K2, K5, K20, K54 and K57, and testing for virulence factors connected to more severe disease in previous studies, was also performed. Data was retrieved from medical records including age, sex, comorbidity, central and urinary catheters, time to adequate treatment, hospital-acquired infection, and mortality, to identify risk factors. The primary end-point was 30- day mortality. The three K. pneumoniae phylogroups were represented: KpI (n = 96), KpII (corresponding to K. quasipneumoniae, n = 9) and KpIII (corresponding to K. variicola, n = 34). Phylogroups were not significantly different in baseline characteristics. Overall, the 30-day mortality was 24/139 (17.3%). Isolates belonging to KpIII were associated with the highest 30-day mortality (10/34 cases, 29.4%), whereas KpI isolates were associated with mortality in 13/96 cases (13.5%). This difference was significant both in univariate statistical analysis (P = 0.037) and in multivariate analysis adjusting for age and comorbidity (OR 3.03 (95% CI: 1.10-8.36). Only three of the isolates causing mortality within 30 days belonged to any of the virulent serotypes (K54, n = 1), had a mucoid phenotype (n = 1) and/or contained virulence genes (wcaG n = 1 and wcaG/allS n = 1). In conclusion, the results indicate higher mortality among patients infected with isolates belonging to K. variicola. The increased mortality could not be related to any known virulence factors, including virulent capsular types or mucoid phenotype.